Why Young People Obey Private Security Guards? A Scenario-Based Study - Moreira, Samuel (Journal of contemporary criminal justice, 2020)
Private security guards (PSG) are prominent social control agents in many contexts of youth attendance. However, studies about youth’s acceptance of PSG authority are scarce. In a scenario-based survey, this study examines youngsters’ compliance with three types of PSG requests and explores factors influencing compliance, particularly instrumental and normative ones. Findings from 631 high school students from the metropolitan areas of Lisbon and Porto (Portugal) suggest that youth typically obey PSG requests, and that perceptions about the role of PSG in protecting public interests and normative judgments about these guards and their requests are important in shaping compliance. Interestingly, variations according to the type of demand are observed. Youth obey more and see their requests as more legitimate when those requests echo shared moral positions.